2015
DOI: 10.1002/2014ja020872
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure and temporal evolution of energetic particle injections in the inner magnetosphere during the 14 July 2013 substorm event

Abstract: Recent results by the Van Allen Probes mission showed that the occurrence of energetic ion injections inside geosynchronous orbit could be very frequent throughout the main phase of a geomagnetic storm. Understanding, therefore, the formation and evolution of energetic particle injections is critical in order to quantify their effect in the inner magnetosphere. We present a case study of a substorm event that occurred during a weak storm (Dst~À40 nT) on 14 July 2013. Van Allen Probe B, inside geosynchronous or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 39 publications
(49 reference statements)
8
78
1
Order By: Relevance
“…They showed that multiple mesoscale injections were observed throughout the storm main phase deep inside the inner magnetosphere and that these injections accounted for a large portion of plasma pressure in the storm time ring current. Gkioulidou et al [2015] reported a dispersionless ion injections at as low as L = 5.5 associated with a sharp dipolarization of magnetic field, similar to dipolarization fronts in the magnetotail. A statistical analysis of dipolarization fronts measured at Van Allen Probes [Liu et al, 2016] showed that as much as 30% of dipolarizations from the magnetotail can penetrate inside geosynchronous orbit.…”
Section: 1002/2016ja023304mentioning
confidence: 76%
See 2 more Smart Citations
“…They showed that multiple mesoscale injections were observed throughout the storm main phase deep inside the inner magnetosphere and that these injections accounted for a large portion of plasma pressure in the storm time ring current. Gkioulidou et al [2015] reported a dispersionless ion injections at as low as L = 5.5 associated with a sharp dipolarization of magnetic field, similar to dipolarization fronts in the magnetotail. A statistical analysis of dipolarization fronts measured at Van Allen Probes [Liu et al, 2016] showed that as much as 30% of dipolarizations from the magnetotail can penetrate inside geosynchronous orbit.…”
Section: 1002/2016ja023304mentioning
confidence: 76%
“…As our nominal case we use an isolated injection/dipolarization event on 14 July 2013 described in Gkioulidou et al [2015]. At 11:21 UT Van Allen Probes spacecraft B observed a large dispersionless increase in the intensities of 80-300 keV protons along with a sharp ∼30 nT dipolarization in the magnetic field at L = 5.5 close to the magnetic equator at dusk.…”
Section: Empirical Model Of Dipolarization Frontsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gerrard et al [2014a] showed quiet time He ion fluxes using data from the Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) instrument on board the Van Allen Probes, and the observations suggest inward radial diffusive motion of He ions which were previously injected into higher L shells. Gkioulidou et al [2014Gkioulidou et al [ , 2015, also using data from the RBSPICE instrument, investigated the ion injections during the ring current buildups and concluded that the small-scale ion injections could make a substantial contribution to the augmentation of the ring current.…”
Section: Introductionmentioning
confidence: 99%
“…The ion fluxes do not exhibit a similar increase, thus, the spacecraft was likely located within the electron boundary of injection but eastward relative to the ion boundary [see Birn et al, 1997b, and references therein]. The injection is observed around the midnight sector where pure electron injections without observations of an ion flux increase are not rare (see statistics in Birn et al [1997a] Gkioulidou et al [2015].…”
Section: Observationsmentioning
confidence: 99%